The PEMANFAATAN TANAMAN LOKAL SEBAGAI PENGENDALI HAMA RAMAH LINGKUNGAN DI DESA MANGGUNG KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Santosa, Sartono Joko; Triyono, Kharis; Maulida, Elly Istiana; Anggreni, Puput (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The utilization of botanical pesticides derived from local plants is an important strategy to support environmentally friendly and sustainable agriculture. This Community Service Program (PKM) was conducted in Betongan Hamlet RT 01/07, Manggung Village, Ngemplak District, Boyolali Regency, involving community members engaged in small-scale crop cultivation. The program was implemented on May 10, 2025, aiming to enhance participants’ knowledge and skills in using local plants as safe and eco-friendly pest control agents. The methods included counseling, training, mentoring, and hands-on practice in producing and applying botanical pesticides. The results indicated increased awareness of the negative impacts of synthetic chemical pesticides and the advantages of botanical alternatives. Participants were able to independently produce and apply botanical pesticides using locally available plant materials. This program contributes to reducing dependency on chemical pesticides and supports the development of sustainable agriculture based on local wisdom.